PEMEKARAN KECAMATAN SUNGAI BEREMAS : LAHIRNYA KECAMATAN KOTO BALINGKA (2003-2011) - Sandra, Feni; Nazmi, Ranti; Meldawati, Meldawati (Pendidikan Sejarah, 2013)
ABSTRACTThis thesis examines the process of expansion Balingka Koto district, who officially split from Beremas River District in 2003 with the issuance of Law No. 38 Year 2003 on the establishment of Balingka Koto district and two other district in Pasaman.The methot of historical research, the firs heuristic is data collection. The second criticism is the source of the tes data. The third interpretation of the combined data with other data. Historiography is the fourth present the results of research in the from of thesis.These results indicate that peoples desire to establish Balingka Koto district itself has existed since the existence of a problem that occurs between the Trenches with Air Bangis Nagari, District Koto Balingka birth is a very long struggle and also a very unique event as the birth of a Balingka Koto district, with the demands of citizens in the Trenches of regents then form a new district with the name Koto Balingka district.Â Keywords: regional growth, power, rule